Dewaterability of sewage sludge conditioned with a graft cationic starch-based flocculant: Role of structural characteristics of flocculant. (1st February 2021) - Hu, Pan; Zhuang, Shuhan; Shen, Shaohang; Yang, Yihan; Yang, Hu
Highlights: Sludge conditioned by series of graft St-based flocculants with various structures. Charge density has more contributions than graft-chain length and its distribution. Dewatering mechanisms are revealed from structural features of flocculant and sludge. Structure-activity relationship of this flocculant is built using a simple model. Optimal dose of this flocculant can be further estimated based on this model. Abstract: Coagulation/flocculation is one of the most extensive and cost-effective pretreatments to improve the dewaterability of sludge in water treatment plants. In this study, three series of graft cationic starch (St)-based flocculants with distinct structural characteristics including charge density (CD), graft-chain length (L), and graft-chain distribution (N) were synthesized by graft copolymerization of [(2-methacryloyloxy-ethyl) trimethyl ammonium chloride] and acrylamide onto St backbone. The structural effects of these St-based flocculants on the sludge dewaterability have been quantitatively analyzed by using a second-order polynomial model according to phenomenological theory. The predicted dewatering performance and optimal dose were fully consistent with the experimental results. On the basis of this established model, the dewatering mechanisms were discussed in detail by combination of the analysis of the changes in filter cake moisture content, specific resistance of filtration, bound water content, compression coefficient, extracellular polymeric substances fractions and components, spatial distributions of proteins and polysaccharides, microstructures of sludge cake, and flocs properties in the dewatering process. This graft St-based flocculant, with the structural characteristics of high CD, long L, and low N, exhibited superior sludge dewaterability because of the enhanced charge neutralization and bridging flocculation effects. Among these three structural factors, CD played a more important role in improvement of sludge dewaterability than L and N due to the dominant effect of charge neutralization. This study provided a better understanding of structure-activity relationship of these grafting modified flocculants, which was of significant guidance for the exploit and design of novel and efficient flocculants for improvement of sludge dewaterability. Graphical abstract: Image, graphical abstract